Kaligrafi (The Control Of Pornography Negative Behavior) As An Efforts To Reduce Pornography Negative Impacts With Antipornography Detection And Potential Motoric Development At Karangbesuki 1 Elementary - Ariani Ariani; Abdullah Bakhrudinsyah Kusuma Wardhana; Rafri Dinda Berbudi Mulia; Athifah Rosi Widiani; Indra Fahrizal; Sabil Prihastomo Seputro (Journal of Innovation and Applied Technology, 2018)
Pornography has big negative impacts on students. KALIGRAFI has purpose to reduce the negative impact of pornography and develop potential motoric on children. This program implemented for 5 months at Karangbesuki 1 Elementary School Malang. The methods used are pretest, giving material, integrated practice, and posttest. Materials given are religious and sexual education and also healthy internet usage. Integrated exercise is done through fun games and grouping of children based on talents and interests to increase the potential of children. The results show that there is a decrease in the number of students exposed to the negative effect of pornography from 57.5% to 17.5% of students. Based on the results, KALIGRAFI make some regeneration and modules as  sustainability of the program so that the program can be maintained and even can be applied easily by the community from elementary school students, educators and parents